On Superconductivity and Superfluidity : A Scientific Autobiography - Ginzburg, Vitaly L. (Springer, 2017)
Chapter 1: On Superconductivity and Superfluidity (What I Have and Have Not Managed to Do), As Well As on the ‘Physical Minimum’ at the beginning of the 21st Century. Chapter 2: Superconductivity and Superfluidity (What was Done and What was Not Done). Chapter 3: A Few Comments on Superconductivity Research. Chapter 4: On the Theory of Superconductivity. Chapter 5: ‘Nobel’ Autobiography (A Supplement to the Nobel Lecture, 2003). Chapter 6: A Scientific Autobiography: An Attempt.